An overview of freight intelligent transportation systems - Mirzabeiki, Vahid (Cranfield University, 2013)
The purpose of this paper is to provide an overview of how the intelligent transportation system (ITS) supports freight transportation operations. A study of the literature on transportation information and communication technology (ICT) and intelligent (or smart) transportation systems has been conducted. Documents of more than 60 companies producing or using intelligent transportation technologies and systems have been reviewed to provide empirical data regarding freight ITSs. Furthermore, direct observations of some of the systems as well as semi-structured and nonstructured interviews with managers of some of the companies have been conducted as secondary sources of empirical data. As a result of studying the companies, a list of nine freight ITSs is generated; it represents the main freight ITSs. Also, different transportation information types that freight ITS work based on their availability are recognised. The results show that vehicle location systems and condition monitoring systems support and use more transportation information types compared to the other freight ITSs.